2009
DOI: 10.1016/j.schres.2009.04.018
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of cannabis use as a risk factor for non-adherence and treatment dropout in first-episode schizophrenia

Abstract: Introduction-Although several studies have reported on cannabis use and adherence for first episode of psychosis patients, the findings remain unclear as to whether cannabis use is a risk factor for poor adherence in young people with first-episode schizophrenia. This study was designed to follow patients' use of cannabis and adherence in a naturalistic setting during the first 12 months of treatment. It examines whether cannabis use is a risk factor for two distinct types of non-adherence: non-adherence to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 38 publications
6
74
1
6
Order By: Relevance
“…However, the studies have reported conflicting results. Miller and coworkers reported that cannabis use was a risk factor for nonadherence to medication and dropout from treatment [66]. Cantwell reported that substance-abusing psychotic patients were younger, more likely to be men and had an earlier age at psychosis onset [67].…”
Section: Reviewmentioning
confidence: 99%
“…However, the studies have reported conflicting results. Miller and coworkers reported that cannabis use was a risk factor for nonadherence to medication and dropout from treatment [66]. Cantwell reported that substance-abusing psychotic patients were younger, more likely to be men and had an earlier age at psychosis onset [67].…”
Section: Reviewmentioning
confidence: 99%
“…Use of substances, including cannabis and alcohol, has been found in several studies to be associated with poor medication adherence (Faridi et al, 2012;Hill et al, 2010;Lambert et al, 2010;Miller et al, 2009), as have a number of other demographic and clinical factors (Hill et al, 2010;Lambert et al, 2010). Furthermore, comorbid substance use has emerged as one of the greatest obstacles to the effective treatment of persons with psychosis; substance use is a risk factor for both poor medication adherence and dropout from treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies suggest a dose-response relationship between severity of substance use and medication adherence rates (Dixon, 1999;Miller et al, 2009;Wade et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The indicators included and extracted are as manifold as in multiple episode patients: lower occupational status, substance abuse, psychopathology (more pronounced delusional symptoms and suspiciousness; Verdoux et al 2000), negative attitudes toward drug treatment and lack of insight (Kampmann et al 2002, Mutsatsa et al 2003, poor premorbid (cognitive) and post-acute (executive) functioning, more pronounced (extrapyramidal) side effects (Robinson et al 2002, Perkins et al 2008, lower expectations regarding the need for or effectiveness of general or drug-specific treatment, treatment with first (vs. second) generation antipsychotics (FGAs / SGAs; Perkins et al 2006), hostility and uncooperativeness, involuntary admission (De Haan et al 2007), poor treatment response, low adherence to preceding treatment, poor cognitive functioning, persisting negative or depressive symptoms, ethnicity (Perkins et al 2008), less social support, living alone, refusing drugs at treatment initiation (Rabinovitch et al 2009), and substance abuse (Perkins et al 2008, Miller et al 2009). …”
Section: Introductionmentioning
confidence: 99%